Eruptive xanthomas as a marker for metabolic disorders: A specific form of xanthoma that reflects hypertriglyceridemia - Sohichiroh Ohtaki; Kenji Ashida; Yuko Matsuo; Kanoko Moritaka; Shimpei Iwata; Ayako Nagayama; Aya Kawaguchi; Hiroshi Koga; Satoko Yoshinobu; Nao Hasuzawa; Seiichi Motomura; Jun Akiba; et al. (Clinical Case Reports, 2022)
Abstract Eruptive xanthomas are skin manifestations associated with hypertriglyceridemia. Accordingly, the improvement of hypertriglyceridemia can ameliorate this condition. We report a case of a patient with type 2 diabetes mellitus who was diagnosed with this skin lesion. Clinicians should be aware that eruptive xanthomas could indicate metabolic disorders associated with atherosclerosis.